PENGARUH KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI PADAPERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIATAHUN 2011 – 2014. - Khairul Adhi Fiandri; Dul Muid (Diponegoro Journal of Accounting, 2017)
This study aims to examine the factors that affect the company's tax evasion or tax avoidance. Factors tested were institutional ownership, firm size and financial performance as a mediating variable.The population in this study were taken from a manufacturing company in the Indonesia Stock Exchange (BEI) in the period 2011-2014 with a total sample of 88 companies. The sampling method used is purposive sampling method. The data used in this research is secondary data obtained from the Indonesian Capital Market Directory (ICMD) and annual financial statements. This study using multiple linear regression technique.The results of the analysis that institutional ownership and firm size affect the mediation variable is the performance of the company. Institutional ownership, company size and financial performance have an impact against tax avoidance.